Contract Employee Information System at Banda Aceh Public Works Department - Febriana, Devi; Idwan, Harry; Imilda (Journal Dekstop Application (JDA), 2022)
This study aimed to develop a Contract Employee Information System for the Banda Aceh Public Works Department, utilizing Microsoft Visual Basic 6.0. In the pursuit of good governance, it is crucial to have a professional and qualified contract workforce to support the effective execution of official duties and public services. However, the department's current processes for data collection and management of contract employees face challenges regarding efficiency and effectiveness. Therefore, this research proposes a desktop-based information system designed to optimize these data collection and management processes. Data was gathered through fieldwork involving interviews and direct observation, supplemented by library research to ensure the validity and success of the study. The findings of this research are expected to positively impact the efficiency and effectiveness of contract employee management within the Banda Aceh Public Works Department